Pengaruh Literasi Keuangan, Kontrol Diri, dan Sosialisasi Keuangan Terhadap Perilaku Menabung - Devi Widya Fitriana; Alfiatul Maulida; Pristin Prima Sari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study was conducted to examine the partial and simultaneous effects of financial literacy, self-control, and financial socialization on the saving behavior of Generation Z in Yogyakarta. The study used a quantitative approach with an associative design. Data collection was carried out using an online questionnaire distributed to 400 respondents from the total population of Generation Z in Yogyakarta. The sampling technique used nonprobability sampling with purposive sampling. The data were analyzed using IBM SPSS Statistics software version 26. The test results showed that: (1) financial literacy had a positive and significant effect on saving behavior. (2) self-control had a negative and significant effect on saving behavior. (3) financial socialization had a positive and significant effect on saving behavior. (4) the three independent variables simultaneously have a significant effect on saving behavior.